Pusat Sejarah Brunei: Beberapa Aspek Perbincangan tentang Koleksi Manuskrip Melayu-Islam : Brunei History Centre: Some Aspects of Discussion on the Collection of Malay-Islamic Manuscripts - Wan Hasbullah, Wan Mohd Dasuki; Mohd Balwi, Mohd Taufik Arridzo; Mat Hussain, Eizah (Journal of Al-Tamaddun, 2023)
Brunei History Centre is one of Brunei Darussalam government's agency that handles Malay manuscript collection and preservation activities. Through inventory and cataloging studies carried out since the 1980s, the involvement of this centre is seen to be in line with other institutions such as the Dewan Bahasa dan Pustaka, the Museums Department, and the Brunei National Archives as manuscript collectors and preservers. However, unlike in the institutions mentioned, the status of the Malay manuscripts collection at the Brunei History Centre has never been mentioned in detail. This article presents a discussion regarding the position of Malay manuscripts in Brunei by analyzing previous studies on the inventory and cataloging of manuscripts, as well as describing the Brunei History Center's manuscript collection in general. This discussion is based on literature research and fieldwork, as well as interviews with agency officials involved. Based on this research, 270 manuscripts were found, which could be categorized into several genres. In addition, a number of untitled manuscripts were also uncovered at the Brunei History Centre. This discussion is pertinent in efforts to establish the existence and potentiality of the Malay manuscript collection at the Brunei History Centre; particularly to foreign researchers in a bid to assist in creating a knowledge base with regards to the collection. In addition, this also serves as a guide for any future undertakings with regard to the appropriate procedures and approaches dealing with those manuscripts. Essentially, this discussion places an emphasis on the fact that the role of this collection could not be disregarded in the scholarly pursuits of Malay manuscripts, mainly from its context as a source of historical analysis as well as in the investigation of Malay-Islamic civilization.